ESTUARINE GIZZARD SHAD NEMATALOSA NASUS (BLOCK) WITHOUT PELVIC FINS - Parimala, S (Indian Journal of Fisheries, 2011)
Abnormal specimens of gizzard shad Nematalosa nasus (Bloch) withoutpelvic flns were record^ from Porto Novo waters.